ANALISIS TINGKAT KESELAMATAN PENYEBERANG MENGGUNAKAN PEDESTRIAN RISK INDEX (PRI) (STUDI KASUS PADA SISWA PENYEBERANG DI SMPN 4 SUKOHARJO) - Kusumastutie, Naomi Srie; Malkamah, Siti (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
The effectiveness of traffic conflict has been already proven in preventively improving safety. Therefore, the aimed of this study was to analyze pedestrian safety based on the pedestrian risk level stated by Pedestrian Risk Index (PRI). Case study was conducted on student pedestrians in SMPN 4 Sukoharjo. The recording of pedestrian crossing was made to get the traffic conflict data. Furthermore, the data was analyzed to obtain the value of Pedestrian Risk Index (PRI). The result of the data analysis showed that there were no differences of the value of PRI based on crosing location and time. However, there was difference of the value of PRI based on the kind of crossing, where individual crossing had higher value of PRI than group crossings. It concluded that group crossings had higher level of safety than individual crossings.